Identification of resistant tomato genotypesusing the gamete technologies - T. I. Saltanovish; A. N. Doncila (Овощи России, 2020)
Relevance. High temperatures are among the environmental factors that negatively affect the development of most crops including tomatoes. Thus, important condition for the realization of potential plant productivity is the heat resistance.Methods of the gamete selection in combination with classical approaches can be used to select resistant genotypes and create initial breeding material with resistance to the temperature factor. Materials and methods.The experiments were carried out with intraspecific hybrids F4 of tomato: Elvira x Milenium, Elvira x Tomis, Elvira x Prestij, Mihaela x Milenium, Mihaela x Tomis, Mihaela x Prestij, Jubiliar х Milenium, Jubiliar x Tomis, Jubiliar x Prestij, Milenium x Elvira, Milenium x  Mihaela. Plants were grown in the field. Flowers were collected, anthers were separated, pollen was isolated. Pollen was heated for 2 or 4 hours at 43°C in the experimental variants. In the control, pollen was maintained at a temperature of 26°C. Then pollen was sown and germinated on a cultural medium. The viability was determined by the length of pollen tubes.Results.A different reaction of pollen grains to temperature influence was established. The main sources of variability and their contribution to the variability of the pollen and seedling traits were determined. The temperature and genotype mainly determine the variability of the gametophyte and sporophyte. More than half of the hybrids combined high indicators of resistance of both pollen and seedlings, formed a larger number of flowers and better set fruits. Thus, tomato genotypes with good indicators of heat-resistance for applying in breeding have been identified based on a complex of methods for assessing the resistance of hybrids using gametophyte and sporophyte characteristics, as well as results of genetic-statistical analysis.